Bibliometric analysis of research trends in competitive advantage and sustainability of MSMEs: A systematic review of Scopus scientific publications - Edi Murdiyanto; Karari Budi Prasasti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The researcher wants to map research with the leading research theme of competitive advantage to assess the sustainability of micro, small and medium enterprises in the world. Design/Methodology- the research uses bibliometric methods by analyzing data collection methods on articles indexed by Scopus with findings of 779 articles on the topic. Data processing is carried out using the VOSviewwer application, which analyzes and provides graphics and images of literature that have been researched clearly and in-depth. Findings- research topics with predetermined themes have been widely researched and published in international journals indexed by Scopus; the topic theme extends to other topics that are still related to the main topic. Many authors wrote together from different agencies and countries and published in many journals with 470 journal publishers. Practical implications: These findings can guide management practitioners, especially those who research the topics raised to develop SMES, where the development of discussions increasingly extends to other topics. Originality/value - only a few have been researched using bibliometrics, which is expected to be used as a guide for future researchers.